Organization development and change - Cummings, Thomas G.; Worley, Christopher G. (Cengage Learning, 2015)
This book blends rigor and relevance in a comprehensive and clear presentation. The authors work from a strong theoretical foundation to describe, in practical terms, how behavioral science knowledge can be used to develop organizational strategies, structures, and processes